Development and Application of Green or Sustainable Strategies in Analytical Chemistry - Naccarato, Attilio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Analytical chemistry is bound to face growing challenges in the future, especially for the quantification of trace analytes in complex matrices. Although the development of increasingly sensitive and specific instrumental techniques has achieved remarkable results, sample preparation is still a fundamental step, often limiting the whole workflow. In the context spawned by the recent international environmental policies that are responsive to the rapport of human activities with the surrounding environment, chemistry cannot hesitate to give its contribution. Almost pioneeringly, in analytical chemistry, we have been talking for some time about "green analytical chemistry", its guiding principles, and the development of eco-friendly analytical approaches. However, the new and still open challenge is advance not only in eco-compatibility but mainly in eco-sustainability, rooting the future of analytical chemistry in new perspective aimed at minimizing the environmental impact of the analytical process by placing environmental cost as a priority aim on par with analytical performance. This is the reprint of a Special Issue that includes contributions focused on the progress in analytical chemistry based on the arguments previously raised and discussed, with a particular reference to eco-compatibility and eco-sustainability. The contributions include the development of low environmental impact methods and/or techniques or their applications.